Project management step-by-step - Richman, Larry L. (Larry Leon), 1955- (New York : Amacom, 2002)
This book spells out the basics of implementing a project management model and encourages critical thinking about how project management can help a company accomplish its business objectives. Offering clear, concise explanations of different project phases, Project management step-by-step also includes six case studies that show how project management works in the real world. Richman's clear, accessible text is augmented with discussion questions, exercises, diagrams, charts, and a comprehensive glossary. Special passwords to free online information for students, instructors, and project management professionals are also included.
Includes bibliographical references (p. [283]-284) and index.
Keywords: Project management